Do the Statutory Types of Venture Investments in Russia’s Regulated Market Conform to Their Economic Essence? - МакушинаЕлена Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Elena Yuryevna Makushina - HSE. Email: emakushina@hse.ru The aim of this research is to propose the definition of «venture capital investments» consistent with their economic substance and to examine the relevant Russian regulations to provide possible solutions for their improvement.In order to accomplish this goal the following issues were raised and solved: identifying the three approaches for defining venture capital investments, analyzing ways of implementing such investments, proposing the private equity market classification, examining the EVCA, NVCA, and RVCA frameworks for venture capital financing and analyzing the new requirements of the Investment Advisers Act of the United States.As a result of the research the following goals were completed: proposing the definition of «venture capital investments»; identifying the key features of the venture capital investments organized as limited partnership; identifying the key features of venture capital investments as opposed to leverage buyout investments; analyzing the main weaknesses of the existing venture capital investments regime in Russia and proposing the possible solutions.